SISTEM INFORMASI TUGAS AKHIR & PRAKTEK KERJA LAPANGAN BERBASIS WEB MENGGUNAKAN METODE UNIFIED PROCESS - Ryan Adiwinata; Eko Adi Sarwoko; Indriyati Indriyati (Department of Informatics, Universitas Diponegoro, 2011)
Final project and job training are the compulsory subject that is organized by Informatics Department Diponegoro University. All registration process, recapitulation and administration about those subjects still have done manually. Moreover, the students and lecturers of informatics departement has not been able to access the latest informations and journals quickly and easily. The Final Project and Job Training Information System is built to solve those problems. This information system was developed using unified process method. Unified process is one of object-oriented software development process which consist of five workflows, requirement, analysis, design, implementation, and test. This information system runs on a web platform using PHP 5 scripting language and MYSQL 5 as database management system that can be accessed anytime and anywhere.The Final Project and Job Training Information System can be used as data, information and administration center about the final project and job training course.